Sustainable development and environmental policy in Egypt - McKenna, Meaghan (AUC Knowledge Fountain, 2013)
This thesis discusses the international law concept of sustainable development. It then assesses the effectiveness of Egyptian policies, laws and regulations with regard to sustainable development and culminates with recommendations on how to move towards more sustainable water management, which is one of the most urgent aspects of sustainable development that needs to be improved. Egypt is confronting an increasing problem of water scarcity. It is a developing economy with high population growth. The effects of climate change are predicted to be particularly severe in North African states, with a decrease in rainfall and increasing desertification and drought. Additionally, in Egypt, every year viable agricultural land is lost to urban encroachment. Yet, Egypt's current policies do not adequately address these issues. Environmental laws are outdated and at times remain unenforced and unregulated. Furthermore, laws do not include sustainable development goals that target poverty reduction and other factors which undermine adherence to current policies. In light of the 25 January 2011 Revolution in Egypt, the creation of new environmental policies that incorporate sustainable development goals, as well as their subsequent enforcement, now seems attainable. As Egypt moves towards democratization, enforcement of law is more likely to translate to sustainable development practices.